Factors driving and influencing the development of serious games - Louise Møller; Poul Kyvsgaard Hansen (Serious Games Society, 2016)
There are a large variety of serious games aimed at infusing knowledge into both teams and organizations. Some games aims at supporting the team in a given project or development process, whereas others aim at widening the knowledge, skills and competences in an organization on a more general level. In the serious game literature most focus and attention is given to the design and development of digital games. However in Denmark, at least, there has been a growing industry of analogue serious games and serious game facilitation, which give evidence to the fact that not all development in the area of serious games happens in terms of the digital versions. This paper investigate these new analog serious games and learning tools in the Danish market with focus on the drivers and influencing factors during their development and the effort of making a business out of the serious games. Empirically, the paper is based on close interaction and semi-structured interviews with some of the key serious game developers in Denmark (plus one in the US), some of them with a portfolio of up to ten serious games. Besides from uncovering some of the basic motivations to design and develop serious games, the paper will show, how the game developers' interaction with the end-users and their different business strategies, influences the way the game is developed.